Primary Science Teaching to Bicolano Students: In Bicol, English or Filipino? - Jualim D. Vela (International Journal of Evaluation and Research in Education (IJERE), 2015)
This study aimed to determine the effects of using the local and mother languages on primary students’ academic performance in science, which is officially taught in English. Using the official language, English, and the two local languages- Filipino, the national and official language, and Bicol, the mother language of the respondents- science lessons were developed and administered to three randomly grouped students.  After each science lesson, the researcher administered tests in three languages to the three groups of students to determine their comprehension of science lessons in the three languages.   The findings indicated that students who were taught using the Filipino language obtained better mean scores in the test compared to students who were taught using their mother language. On the other hand, students who were taught using the English language obtained the lowest mean scores.  Furthermore, the results revealed that the Bicol speaking students prefer the Filipino language during class discussions, recitations, in following their teacher’s instructions during science related classroom activities, and in doing their homework.